Respuesta :

Answer:

0.5

Step-by-step explanation:

Plug in -1 as x into the function:

f(-1) = -1 + 3/2

f(-1) = 0.5

[tex]\bf \underline{ \underline{Given : }}[/tex]

f(x) =x + 3/2

[tex]\bf \underline{ \underline{To \: be \: calculated : }}[/tex]

what is the value of f(-1) ?

[tex] \bf \underline{ \underline{Solution : }}[/tex]

[tex] \sf{f(x) = x + \dfrac{3}{2} }[/tex]

[tex] \rightarrow \sf {f( - 1) = ( - 1) + \dfrac{3}{2} }[/tex]

[tex] \rightarrow \sf{f( - 1) = \dfrac{ - 2 + 3}{2} }[/tex]

[tex] \rightarrow \sf{f( - 1) = \dfrac{ 1}{2} }[/tex]

[tex] \rightarrow \sf {f( - 1) = 0.5}[/tex]